NEGOSIASI IDENTITAS KULTURAL MELALUI BAHASA - Nuril Hidayah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2018)
Pendalungan is a hybrid culture established because of intensive contact between two dominant culture namely Javanese and Madurese. Those cultures represent their ethnicity. Beside the two, there are another ethnicity like Chinese and Arabs. Multilingual interaction has permeated everyday life of this community especially in the domain of commerce where all ethnic groups gathered. Language accommodation has become an effective strategy for intercultural interaction in this community. The purposes of this study were to describe the form of language selection, to describe the pattern of language accommodation, to describe the causes of language accommodation, and to describe the functions of language accommodation in the commercial domain of intercultural interaction in Pendalungan community. The data were collected by using observation method by applying the technique of taping as the basic technique. Then continued with advanced techniques such as observe-involve-participate, free observe-involve-participate, recording techniques, taking notes, and then complemented by interview results. The data were analyzed by using ethnographic methods and taking some sociolinguistic theories into account, like domain theory, language accommodation theory, and speech function theory. The study has resulted some findings. First, the forms of language selection in the commercial domain of intercultural interaction in Pendalungan community in Probolinggo City are single code, code switching and code mixing. The factors underlying the language selection are age, social status, ethnic identification, speech setting. The language selection has directive, referential, expressive, and phatic functions.